1996
DOI: 10.1177/1045389x9600700604
|View full text |Cite
|
Sign up to set email alerts
|

TIG Welding and Shape Memory Effect of TiNi Shape Memory Alloy

Abstract: In the present study, with respect to TIG welding for a TiNi shape-memory alloy wire and sheet, the optimum welding schedule was decided based on the breaking load of the weld and its standard deviation. By performing the cyclic loading-unloading and heating-cooling tests in the neighborhood of the weld, the shape memory effect was investigated. In order to investigate the shape memory effect in detail, the tensile properties of the weld metal and heat-affected zone were discussed. Based on the results, the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(20 citation statements)
references
References 8 publications
0
19
0
1
Order By: Relevance
“…Interstitial phases (based on H, N and O), however, were observed due to insufficient protection of the molten pool. Ikai et al [29] several years later resumed this process and observed a decrease in the mechanical properties of the welded joints. In particular, the welded material presented a high irrecoverable strain during cycling tests for a total of 50 cycles at 4% strain.…”
Section: Tungsten Inert Gas (Tig)mentioning
confidence: 99%
“…Interstitial phases (based on H, N and O), however, were observed due to insufficient protection of the molten pool. Ikai et al [29] several years later resumed this process and observed a decrease in the mechanical properties of the welded joints. In particular, the welded material presented a high irrecoverable strain during cycling tests for a total of 50 cycles at 4% strain.…”
Section: Tungsten Inert Gas (Tig)mentioning
confidence: 99%
“…Therefore, there has been a strong effort to find a suitable joining process to minimize the change in properties resulting from welding. Conventional fusion welding of TiNi reduces the shape-memory properties due to severe metallurgical conversion in the heat-affected zone and fusion zone 2) however, a recent report showed that there is an improvement in the joining of TiNi SMAs by tungsten inert gas (TIG) welding. 3) Laser welding is the most common joining process of TiNi SMAs because of its high energy density and very low heat input, which leads to minimizing the welding distortion.…”
Section: Introductionmentioning
confidence: 99%
“…Since 1980, the joining of TiNi SMA has become the hot spot and front edge in the joining research field. Great attention has been given to the influencing of joining method and procedure on structure and properties of the homogeneous joint (joining TiNi SMA to TiNi SMA), but the study on joining TiNi SMA to other materials was very little [4][5][6][7][8][9][10][11]. Authors studied microstructures and properties of TiNi SMA and SS joint by fusion welding process [12].…”
Section: Introductionmentioning
confidence: 99%